Age-Related Hypertension: A Cross-Sectional Analysis of Influencing Factors - Arifia Damayanti; Nur Isnaini (Proceedings Series on Health & Medical Sciences, 2024)
Background:Hypertension is characterized by high blood pressure, with systolic pressure above 140 mmHg and diastolic pressure above 90 mmHg, and it commonly affects the elderly population. There are two types of risk factors for hypertension, namely modifiable and non-modifiable factors. Method: This research employed a quantitative method with an analytical survey design using a case-control method. The sample size consists of 60 respondent, selected using a purposive sampling technique. Results: Statistical tests indicated a significant correlation for variables such us family history (?-value 0.0001), salt consumtion (?-value 0.0001), stress/anxiety (?-value 0.005), and compliance with a healthy lifestyle (?-value 0.003), with the occurrence of hypertension. On the other hand, age (?-value 0.278), gender (?-value 0.091), obesity status (? value 0.390), smoking status (?-value 0.243), and caffeine/coffee consumtion habits (?-value 0.196) did not show any significant correlation with hypertension occurrence. Conclusion: Family history, salt consumtion, stress/anxiety, and compliance with a healthy lifestyle are factors affecting the occurrence of hypertension in the elderly at Sokaraja 1 Public Health Care Center. However, age, gender, obesity status, smoking status, and caffeine/coffe consumtion habits do not contribute to hypertension.